Muela, Julián; Yllera, Alicia; Lafarga, Francisco; Martínez,Caridad (1994): Repertorio de Estudios Franceses en la Universidad Española. - López Jiménez, Luis (Thélème. Revista Complutense de Estudios Franceses, 1995)
Sin resumen